Effect of acute intermittent hypoxia treatment on ventilatory load compensation and magnitude estimation of inspiratory resistive loads in an individual with chronic incomplete cervical spinal cord injury. (January 2016) - Jaiswal, Poonam B.; Tester, Nicole J.; Davenport, Paul W.
Abstract : Context: Spinal cord injury (SCI) causes disruption of the efferent input to and afferent input from respiratory muscles, which impairs respiratory motor and sensory functions, respectively. This disturbs the injured individual's ability to respond to ventilatory loads and may alter the respiratory perceptual sensitivity of applied loads. Acute intermittent hypoxia with elevated CO2 (AIH treatment) has been shown to induce ventilatory long-term facilitation in individuals with chronic SCI. This study evaluated the effect of ten days of AIH treatment on ventilatory load compensation and respiratory perceptual sensitivity to inspiratory resistive loads (IRL), in an individual with chronic, incomplete cervical SCI. Methods: Case report and literature review. Findings: We report a case of a 55-year-old female with a C4 chronic, incomplete SCI (American Spinal Injury Association Impairment Scale D). The subject underwent evaluation at four time-points: Baseline, Post Sham, AIH Day 1 and AIH Day 10. Significant improvements in airflow generated in response to applied IRL were found after AIH treatment compared to Baseline. There were no significant changes in the respiratory perceptual sensitivity to applied IRL after AIH treatment. Clinical relevance: Rehabilitative interventions after SCI demand restoration of the respiratory motor function. However, they must also ensure that the respiratory perceptual sensitivity of the injured individual does not hinder their capability to compensate to ventilatory challenges.